2020
DOI: 10.21037/apm-20-1574
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Klebsiella pneumoniae cfDNA in pleural fluid and its clinical value

Abstract: Background: Klebsiella pneumoniae (KP) is an important opportunistic pathogen that can easily cause pneumonia and pleural effusion when body resistance is reduced. However, the positive rate of KP detected from clinical pleural effusion by traditional methods, including bacterial culture, is meager. Therefore, new detection methods are urgently needed to improve the positive detection rate of KP and other bacteria in pleural effusion.Methods: Simulated pleural fluid of KP infection was first set up. Then circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Factors such as infection, intestinal microecological imbalance, and immune barrier disruption can cause conditional pathogenesis of Klebsiella pneumoniae . Previous studies have shown that Klebsiella pneumoniae -related sepsis can significantly increase the risk of systemic multi-site infections ( Li et al., 2021 ), and thoracoabdominal membranes are the potentially affected tissues ( Ren et al., 2020 ; Ameer et al., 2022 ). Interestingly, Klebsiella pneumoniae was only detected in multiple samples at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as infection, intestinal microecological imbalance, and immune barrier disruption can cause conditional pathogenesis of Klebsiella pneumoniae . Previous studies have shown that Klebsiella pneumoniae -related sepsis can significantly increase the risk of systemic multi-site infections ( Li et al., 2021 ), and thoracoabdominal membranes are the potentially affected tissues ( Ren et al., 2020 ; Ameer et al., 2022 ). Interestingly, Klebsiella pneumoniae was only detected in multiple samples at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…A research set up K . pneumoniae cell-free DNA (cfDNA) detection system, but the clinical application value still needs further study ( 8 ). Despite extensive research over the past few decades, the pathophysiology of K .…”
Section: Introductionmentioning
confidence: 99%